The effect of spraying Basfoliar Kelp SL and calcium on some physiological and physical characteristics of date palm fruits, Phoenix dactylifera L, Al-Shwaithi cultivar - Wead Karim Abdel Raheel Al-Atabi; Ahmed Dinar Al-Asadi (University of Thi-Qar Journal of agricultural research, 2024)
This study was conducted during the 2023 growing season in one of the private orchards in Thi Qar Governorate, with the aim of studying the effect of spraying fruits with concentrations of Basfoliar Kelp SL (0, 2 and 4) ml L-1 and calcium (0, 2.5 and 5) ml L-1 and their interactions in Some physiological and physical characteristics of date palm fruits, Al-Shwaithi variety, at the Rubab stage. The experiment was carried out as a factorial experiment according to a completely randomized block design with five replications to calculate the studied characteristics. Concentrations of Basfoliar Kelp SL and calcium were sprayed 21 days after pollination and upon completion of fruit set, and 6 sprays between one another (15 days) and until fruit growth was completed and the coloring phase began. The results can be summarized as follows. The concentration of seaweed extract Basfoliar Kelp SL (4 ml L-1) showed a significant increase in most of the physiological and physical traits studied, and the highest rates were recorded for: maturity rate (87.68%), fruit length (3.76 cm), fruit diameter (2.41 cm), and fruit weight. (10.38 cm) and shoot weight (8.28 kg), in addition to the concentration (4 ml L-1) recorded the lowest rates, with a significant difference in the percentage of fruit drop (12.94%). The calcium concentration (5 ml L-1) showed a significant increase in most of the physiological and physical traits studied, and the highest rates were recorded in the maturity rate (86.38%), fruit length (3.68 cm), fruit diameter (2.38 cm), fruit weight (10.15 g), and bunch weight ( 7.61 kg) for the Rubab stage, in addition to recording the lowest rates with a significant difference in the percentage of fruit drop (10.66%). As for the effect of the interaction parameters between Basfoliar Kelp SL (4 ml L-1) and Calcium (5 ml L-1), it was significant in giving the highest rates of physiological and physical characteristics during the retag stage.